International Jurisdiction in Criminal Matters - Softić, Sakib (Kriminalističke teme, 2013)
The issue of jurisdiction to prosecute persons responsible for serious violations of international law is in a constant progress and occasionally requires reconsideration in light of the emergence of new rules of international law and their application in practice of international and national criminal courts. The author has researched the principles on which the jurisdiction has been established by using original international documents, the relationship between international and national jurisdictions, views of the various judicial bodies occupied in their application in specific cases as well as their understanding of the leading legal experts in this field. Then he described and explained them separately and in relation to each other so that the work provides a comprehensive picture of the state of theory and practice in this are. The principles on which jurisdiction was founded in criminal matters arising from international custom, international treaties and national legislation. There are no rules of customary international law of general character which obliged the state to exercise jurisdiction on any of these grounds. Yet in those areas in which international conventions provide for such an obligation of the state one might say that such rules are emerging.